Wind Dynamics Over a Highly Heterogeneous Oasis Area: An Experimental and Numerical Study. Issue 16 (18th August 2018) - Liu, Rui; Liu, Shaomin; Yang, Xiaofan; Lu, Hui; Pan, Xiaoduo; Xu, Ziwei; Ma, Yanfei; Xu, Tongren
Abstract: Oases are unique heterogeneous landscapes that coexist within the Gobi desert in the arid and semiarid regions, which are vital for agricultural production and economic development. The heterogeneity of the land surface with vegetation will significantly influence the wind dynamics and airflow characteristics. The current study utilized an integrated approach, combining the computational fluid dynamics (CFD) method with the k ‐ ɛ turbulence model and high‐resolution ground‐measurement data to analyze the wind dynamics over an oasis. Specifically, (1) the Weather Research and Forecast model (WRF) data were used as boundary conditions to initiate the simulations; (2) the canopy leaf area density estimated from airborne laser scanning data was added as the source terms of the momentum and turbulence transport equations, which represented the highly heterogeneous vegetation structures in the oasis area. CFD‐simulated wind field results agreed well with the flux observation matrix data (17 tower measurements in a 5.5 km × 5.5 km experimental area). The spatial and temporal variations of wind fields affected by heterogeneous land surfaces were successfully captured. The CFD‐simulated wind fields also clearly showed the "wind shield effect" over highly heterogeneous land surfaces, wherein the existence of shorter and longer wind speed reduction areas at the windward and leeward sides of the shelterbelts contribute to protecting farmlands and orchards from wind erosion. In addition, the current approach of estimating aerodynamic roughness length ( z 0m ) based on high‐resolution CFD‐simulated wind profiles was demonstrated to be a promising method of capturing wind dynamics over heterogeneous surfaces. Key Points: High‐resolution CFD simulations were performed incorporating WRF and ALS data then validated by high‐resolution ground measurements Wind dynamics and "wind shield effect" caused by heterogeneous land surfaces were systematically analyzed based on CFD simulations Regional aerodynamic roughness length was estimated via simulated wind profiles to capture wind dynamics over heterogeneous surfaces